Hubungan Dukungan Suami dengan Kepatuhan Kunjungan Antenatal Care (ANC) Ibu Hamil di Puskesmas Godean 1 - Desiana Rena; Sarwinanti Sarwinanti; Diah Nur Anisa (Lembaga Pengembangan Kinerja Dosen, 2026)
Compliance with (ANC) visits is an essential effort to reduce the risk of pregnancy complications and maternal mortality. One of the factors influencing ANC visit compliance is husband’s support. This study aimed to determine the relationship between husband’s support and compliance with visits among pregnant women at Godean 1 Public Health Center, Sleman Regency. This study employed a quantitative analytic design with a cross-sectional approach. A total of 65 pregnant women were selected using purposive sampling. Data on husband’s support were collected using a questionnaire, while ANC visit compliance was verified through the Maternal and Child Health (MCH) handbook and medical records. Data were analyzed using Spearman’s rho test. The results showed that most respondents received husband’s support (83.1%) and were compliant with ANC visits (86.2%). There was a significant relationship between husband’s support and ANC visit compliance, with a p-value of 0.000 and a correlation coefficient of 0.888, indicating a very strong relationship. This study concludes that husband’s support plays an important role in improving compliance with visits. Therefore, increasing husband involvement in maternal health services is necessary to support the success of programs.